Homeless Media Islam dan Kontestasi Narasi Keagamaan di Ruang Siber - Moebin, Amrullah Ali; Widodo, Agus; Cahyono, Muchamad Rudi (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This article examines the phenomenon of homeless Islamic media and the contestation of religious narratives in cyberspace. This study employs a qualitative approach with a case study design, utilizing in-depth interviews, digital observation, and online document analysis. The findings reveal that religious contestation in the digital sphere is shaped by engagement mechanisms, algorithmic visibility, and religious personal branding rather than solely by traditional forms of legitimacy such as scholarly lineage. Religious narratives are produced, exchanged, and contested within the logic of platform ecosystems that prioritize popularity as a key metric. Under these conditions, religious authority is no longer hierarchical but becomes distributed and continuously negotiated within digital networks. These dynamics affirm that homeless Islamic media constructs a new configuration of religious contestation and legitimacy one that is plural, competitive, and network-based within cyberspace.